On the perceived usefulness and effectiveness of Eduflow as a supplementary tool for online writing instruction - Natasha Stojanovska-Ilievska (My University, 2023)
This paper centres around the use of Eduflow, a novel online learning management system (LMS) which was introduced in a university-level Academic Writing course in response to the challenges brought about by the mandatory switch from face-to-face to online writing instruction (OWI) over the course of the COVID-19 pandemic. In this paper, Eduflow is piloted with a group of second-year university students of English language and literature at Ss. Cyril and Methodius University in Skopje. These students chose to fulfil their Academic Writing course requirements by compiling a writing portfolio. The rationale behind the use of this platform was the assumption that it would facilitate the online management of all the stages of the essay writing process: Writing a first draft, doing a peer review of essays created by fellow students, considering the comments received from fellow students, reflecting on one’s own writing by doing a self-review, and finally, submitting the final version. The relentlessness of the pandemic led to the continuous application of this learning management system over the course of two entire academic years, each year with a different group of students. An online survey on the perceived usefulness and effectiveness of Eduflow was administered among the second generation of students who used this platform. As this small-scale analysis demonstrates, despite experiencing some easily resolvable minor technical difficulties, these students generally found Eduflow effective and useful as a supplementary tool for online writing instruction and showed particular appreciation for the collaborative peer review experience.
Keywords: online writing instruction, learning technologies, collaborative learning, academic writing, learning management system